Prenatal aspects in spinal muscular atrophy: From early detection to early presymptomatic intervention. (November 2018) - Tizzano, Eduardo F.; Zafeiriou, Dimitrios
Abstract: With the recent advances in spinal muscular atrophy therapies, the complete scenario of standard of care and following up is changing not only in the clinical field with new phenotypes emerging but also with new expectations for patients, caregivers and health providers. The actual evidence indicates that early intervention and treatment is crucial for better response and prognosis. Knowledge of the prenatal and pre-symptomatic postnatal stages of the disease are becoming essential to consider the opportunities of timely diagnosis and to decide the earliest therapeutic intervention. Highlights: With recent therapeutic advances, the landscape of spinal muscular atrophy has changed. Early intervention and treatment is crucial for better response and prognosis. Knowledge of the prenatal and pre-symptomatic SMA is essential. Early diagnosis by newborn screening imply moving towards pre-symptomatic intervention. Ethical issues are considered on decision making by the families.